PV HOSTING CAPACITY ANALYSIS USING QUASI-STATIC TIME SERIES SIMULATION, STUDY CASE IN BANDAR LAMPUNG, INDONESIA - Prasetyo Susilo Putra, Reynaldi
This study analyzes the hosting capacity of rooftop photovoltaic (PV) systems in the distribution network of Bandar Lampung, Indonesia, using the Quasi-Static Time Series (QSTS) simulation method. With the increasing penetration of PV in distribution networks, this research evaluates the impact of PV on voltage profiles, power flow, and the potential for Reverse Power Flow (RPF). The QSTS method is employed to analyze daily load profiles and solar irradiance variations over a 24- hour period, ensuring PV integration does not exceed network operational limits. Results indicate a maximum hosting capacity of 44.85 MW with an average transformer hosting capacity of 0.066 MW. The study highlights the importance of dynamic analysis for optimizing renewable energy integration into distribution networks.